Sistem Informasi Manajemen Data Inventaris Toko Berbasis Website - Kurniawati, Dwi Otik; Zaki, Abidillah; Luthfiah, Khansa (Lembaga Dongan Dosen, 2024)
Rapid developments in the field of information and communication technology have driven progress in various sectors, including government and private organizations. Technology, especially web-based applications, is increasingly being used to increase work effectiveness and efficiency. Entity Relationship Diagram (ERD) is a tool commonly used in database system design to describe the relationships between entities and attributes in a system. Databases play an important role in storing and managing production information, which allows companies to access data quickly, accurately and safely. This supports timely decision making and ensures centralized data management. Before designing the database, the researcher carried out a problem analysis first at the Istikah Shop. So far, the shop does not have a database. The shop only does manual bookkeeping, especially for stock items in the shop. This method is considered time consuming and prone to human error. The research provides a solution by designing a database for the new Istikah Shop system. The design of the database model makes it easier to manage stock data. This database model design can then be submitted to the Istikah Store management to serve as a reference and reference source for further inventory system development. This design can help developers design the data structures and tables needed in the system. The resulting interface implementation is in accordance with the design. The system can be used well. That way, this system can be a solution for Istikah Stores in terms of inventory